2004
DOI: 10.1038/sj.onc.1208274
|View full text |Cite
|
Sign up to set email alerts
|

Parafibromin, product of the hyperparathyroidism-jaw tumor syndrome gene HRPT2, regulates cyclin D1/PRAD1 expression

Abstract: Parafibromin is the 531-amino-acid protein product encoded by HRPT2, a putative tumor suppressor gene recently implicated in the autosomal dominant hyperparathyroidism-jaw tumor familial cancer syndrome, sporadic parathyroid cancer, and a minority of families with isolated hyperparathyroidism. Parafibromin contains no identified functional domains but bears sequence homology to Cdc73p, a budding yeast protein component of the RNA polymerase II-associated Paf1 complex. This study addressed the expression and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
140
3
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(161 citation statements)
references
References 28 publications
9
140
3
5
Order By: Relevance
“…Concomittantly, HA-tagged species of wild-type parafibromin (lane 3), the R222X mutant lacking the C-terminal PAF1-binding domain (lane 4) and the newly identified K34Q mutant derivative (lane 5) were efficiently produced. Consistent with previous findings demonstrating that parafibromin overexpression is correlated with decreased cyclin D1 expression (Woodard et al, 2005), we observed that downregulation of endogenous parafibromin caused an increase in cyclin D1 protein levels (compare lane 2 and 1). Re-expression of HA-tagged wild-type parafibromin reverted this effect (lane 3).…”
Section: Functional Analysis Of the Parafibromin Mutant K34qsupporting
confidence: 92%
See 2 more Smart Citations
“…Concomittantly, HA-tagged species of wild-type parafibromin (lane 3), the R222X mutant lacking the C-terminal PAF1-binding domain (lane 4) and the newly identified K34Q mutant derivative (lane 5) were efficiently produced. Consistent with previous findings demonstrating that parafibromin overexpression is correlated with decreased cyclin D1 expression (Woodard et al, 2005), we observed that downregulation of endogenous parafibromin caused an increase in cyclin D1 protein levels (compare lane 2 and 1). Re-expression of HA-tagged wild-type parafibromin reverted this effect (lane 3).…”
Section: Functional Analysis Of the Parafibromin Mutant K34qsupporting
confidence: 92%
“…Mutation in parafibromin have been recently linked to the control of cyclin D1 expression (Woodard et al, 2005). Thus, we next determined whether the K34Q parafibromin mutant is defective in this regard.…”
Section: Functional Analysis Of the Parafibromin Mutant K34qmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, transient over-expression of parafibromin inhibits cyclin D1 expression whereas downregulation of parafibromin using small interfering RNA (siRNA) leads to premature entry of cells into S phase (Woodard et al, 2004;Yart et al, 2005). In addition, parafibromin is associated with a Set-1-like histone methyltransferase (HMTase) complex that methylates H3 on lysine 4, and thereby initiates transcription by chromatin modification and activation of RNA polymerase II (Rozenblatt-Rosen et al, 2005;Yart et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as part of this protein complex, parafibromin may regulate posttranscriptional events and histone modification. In keeping with such roles parafibromin has been reported to be a nuclear protein by two studies (Tan et al, 2004;Rozenblatt-Rosen et al, 2005), although one other study has reported that parafibromin may also be in the cytoplasm (Woodard et al, 2004).…”
Section: Introductionmentioning
confidence: 87%